Chemistry of peptide bond formation - Green, Rachel (Henry Stewart Talks, 2008)
Fundamental processes during protein synthesis, Peptidyl transfer catalysis by RNA-rich active site, Ribosome structure solution provided new insights, Peptide bond formation and peptide release, Active site of the ribosome, Universally conserved nucleotides of the active site, Affinity tag purification of mutant ribosomes, Active site mutations and rates of peptidyl transfer, A-site substrates: tRNA vs. puromycin, "Uninduced" state of ribosome and P-site substrate, A-site substrates-induced conformational changes, Peptide release activity of variant ribosomes, RF catalysis in the large subunit, RF conserved amino acids in bacteria, Consequences of RF1 site-directed mutations, Nucleophile partitioning, Mutants that lost water specificity, RF components functioning in activating hydrolysis, Regulation of translation post-initiation
Archived at 2020/08/13